2002
DOI: 10.1126/science.1076347
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall Variability, Carbon Cycling, and Plant Species Diversity in a Mesic Grassland

Abstract: Ecosystem responses to increased variability in rainfall, a prediction of general circulation models, were assessed in native grassland by reducing storm frequency and increasing rainfall quantity per storm during a 4-year experiment. More extreme rainfall patterns, without concurrent changes in total rainfall quantity, increased temporal variability in soil moisture and plant species diversity. However, carbon cycling processes such as soil CO2 flux, CO2 uptake by the dominant grasses, and aboveground net pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

63
863
9
18

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 977 publications
(953 citation statements)
references
References 21 publications
63
863
9
18
Order By: Relevance
“…Apart from extremes, changes in the seasonal distribution of climate factors may be decisive. This is particularly evident for water-carbon-cycle interactions, where changes in the frequency or timing of rainfall without changes in the annual total may have profound effects on ecosystem productivity 12 , as these factors determine whether the water will be used by plants and transpired, or will just run off or evaporate.…”
Section: Climate Variability and Extremesmentioning
confidence: 99%
“…Apart from extremes, changes in the seasonal distribution of climate factors may be decisive. This is particularly evident for water-carbon-cycle interactions, where changes in the frequency or timing of rainfall without changes in the annual total may have profound effects on ecosystem productivity 12 , as these factors determine whether the water will be used by plants and transpired, or will just run off or evaporate.…”
Section: Climate Variability and Extremesmentioning
confidence: 99%
“…Studies that employ multi-scale approaches are valuable in demonstrating the importance of a holistic understanding of ecosystem responses to changing climatic variability [128] and extremity [4,14,129]. The magnitude of response to a climate extreme will likely vary with the ecological level of organization (e.g.…”
Section: Integrating Responses Across Ecological Scalesmentioning
confidence: 99%
“…Aboveground net primary production (ANPP) is the main carbon fixation pathway, and even though its responses to changes in the amount of precipitation have been well studied, knowledge about the effect of precipitation variability on ANPP is rather poor, especially at the interannual to decadal time scales. A few short-term experiments focused on the effect of intra-annual precipitation variance and reported contrasting results, with null or positive effects in arid systems and negative effects in mesic systems (11)(12)(13)(14). A modeling exercise found that increased interannual precipitation variability and temperature in the Tibetan Plateau led to productivity reduction in grasslands (15).…”
mentioning
confidence: 99%